If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1y = -1x + -4 Reorder the terms: -1y = -4 + -1x Solving -1y = -4 + -1x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-1'. y = 4 + x Simplifying y = 4 + x
| b^2=2b | | t(t-7)=18 | | x^2-x+649=0 | | -2(x+5)+4x= | | -10-2x=x+5 | | y=x^2+3x-5 | | 10x-3x-9+3-x=18 | | 17x-8=12x+33 | | 4x-1=3x+4 | | 20t^2=64+64t | | 2x+7=4x+7 | | 4x^2-7x+13=6x+3 | | 5k-4k+6= | | 20t^2=64+64 | | 10+3y=-9 | | 6x^2-38x-80=0 | | -2c+12=2c-6+6c-12 | | -6x+8=14-3x | | b+b+b+6=6b+5-2b+9 | | y^2+7y-30=0 | | 4x-2=-2x-56 | | 7x-10=-37-2x | | 8k-6+3k-2k+3=4*33 | | 6-5x-2x=34 | | 6w^2+33w-18= | | 2d-8-5d=-3d-2d+6 | | 15=3.4n-2(n-4) | | (3x)+(4x-24)=180 | | x^2+1045x+14278=0 | | P=100-0.5q | | 3c-6+2c=10c-2c+6 | | 5u+6v-3(3u-2v)= |